Improving Skills Development in the Informal Sector: Strategies for Sub-Saharan Africa - Adams, ArvilV. (World Bank, 2015)
The informal sector of Sub-Saharan Africa is comprised of small and household enterprises that operate in the non-farm sector outside the protected employment of the formal wage sector. The sector was identified 40 years ago by the ILO representing a pool of surplus labor that was expected to be absorbed by future industrialization, but rather than gradually disappearing, it has become a persistent feature of the region?s economic landscape accounting for a majority of jobs created off the farm. Acknowledging its potential as a source of employment for the region?s expanding workforce and improving its productivity and earnings is recognized as a priority for poverty reduction. This study examines the role played by education and skills development in achieving this objective.